Integrative rehabilitation in the treatment of lumbosacral muscle strain in elite trampoline athletes: a pilot study - Ma, Jia-Yin; Wu, Jia-Jia; Zhang, Jing; Zhao, Qing; Shen, Feng-Tao; Feng, Ling; Zhang, Guo-Hui; Zhu, Yi; Xu, Jian-Guang (Frontiers in Sports and Active Living, 2024)
Background Lumbosacral muscle strain (LMS) is common in Chinese elite trampoline athletes. Advanced lumbar muscle activation is necessary for postural control before upper extremity voluntary movements, called anticipatory postural adjustment to reduce internal postural interference (IPI). The potential of delayed lumbar muscle activation has been reported in patients with non-specific LBP (NLBP) in response to IPI. However, it remains unknown whether this effect exists in elite trampoline athletes. There is also limited literature reporting the rehabilitation of LMS in this population. This study first aimed to explore whether elite trampoline athletes with LMS experience delayed activation of lumbar muscles under IPI. The secondary aim was to preliminarily evaluate an integrative rehabilitation program's effectiveness. Materials and methods Ten elite trampoline athletes with LMS were recruited and received 10 sessions of integrative rehabilitation, including extracorporeal shock wave therapy, acupuncture, Tui-na, and spine function exercises. At baseline and after all sessions, the relative activation time of the lumbar muscles under IPI in a modified rapid arm-rise test was used as a primary outcome measure. The secondary measures included a visual analog scale (VAS) and a questionnaire to assess low back pain (LBP) and athletic training performance. Results The relative activation time of the lumbar muscles under IPI was delayed at baseline, but significantly decreased after the intervention (P < 0.05). The VAS was significantly decreased after the intervention (P < 0.05). There was no significant correlation between the difference in VAS and in activation time of the lumbar muscles before and after the intervention (P > 0.05). Conclusions Elite trampoline athletes with LMS had delayed activation in their lumbar muscles under IPI. Integrative rehabilitation was effective in LBP relief and neuromuscular control of the lumbar muscles, and impacted positively on training performance. Future studies with a larger sample size, a control group, and long-term follow-ups are needed to further examine the efficacy of integrative rehabilitation in elite trampoline athletes with LMS. Additionally, the application of this approach in athletes with LMS or LBP in other sports, particularly those involving IPI, should be explored.